Gestión de proceso administrativo en el departamento sala de proyectos en el GAD Parroquial Rural de Caracol, periodo fiscal 2023. - Mazacon Brian, Ahilis Olga (2024)
Management of administrative processes is fundamental to the effective functioning of the project space department, this means identifying, documenting, monitoring and optimizing key processes involved in daily operations, some important management processes include project planning and scheduling, resource allocation, the acquisition of equipment and materials, budget management, quality control, risk management, communication between teams and document management. Department managers must ensure that these processes are clearly defined, that employees understand their responsibilities, and that procedures are followed appropriately. It allows you to coordinate tasks, optimize resource consumption, meet deadlines and ensure high-quality results. Good process management also requires monitoring key metrics such as costs, productivity, and customer satisfaction. Processes should be periodically evaluated and, if necessary, optimized. Automation and digital tools help increase efficiency. Effective management of project office administrative processes is essential to coordinate activities, use available resources, achieve objectives and achieve results that meet client and management expectations.